Fatores de risco para saúde mental de médicos veterinários clínicos - Gresele, Bianca Stevanin (2024)
The focus of this study was to investigate the risk factors for the mental health of Brazilian small animal veterinarians. For this purpose, burnout syndrome, compassion fatigue and suicidal ideation were used as evaluation criteria. The research also investigated how sociodemographic differences and self-care habits are correlated with the mental health status of professionals. To this end, a sequential mixed method was adopted, which was applied online, in which participants in the quantitative stage helped identify participants in the qualitative stage. Quantitative data, treated statistically, were obtained through a questionnaire that included 32 sociodemographic and investigative questions about the stressors of the profession, the Beck Suicidal Ideation Scale, the Proqol-BR Scale and the Maslach Burnout Inventory Scale. In the second stage, a semi-structured interview with 5 questions was used, which investigated the veterinarians' feelings towards the profession and the self-care habits they practice. Participants in the first phase were 1,074, the sample included small animal clinical veterinarians from all over Brazil. The second phase had 18 participants, separated into three groups, classified as high, medium and low risk. Among the results, it was found that veterinarians with higher rates of burnout syndrome, compassion fatigue and suicidal ideation are women, young, without specialization, who work in the area of general practice. According to the participants, the three main stressors associated with the profession are: the emotional exhaustion generated by the services, serving emotionally shaken clients and balancing personal and professional lives. Finally, the professionals with the highest rates are those who do not have a self-care routine and who cannot balance their personal and professional lives